SCD2-mediated monounsaturated fatty acid metabolism regulates cGAS-STING-dependent type I IFN responses in CD4+ T cells - Toshio Kanno (Nature Portfolio, 2021)
Kanno et al. demonstrate that decreased monounsaturated fatty acid in CD4 + T cells following Scd2 deletion boosts the induction of the antiviral response via activation of the cGAS-STING pathway in mice. This study highlights the important interaction between fatty acid metabolism and the acquired immune response.